THE EFFECT OF DEBT-TO-ASSET RATIO, STOCK PRICE, AND RETURN OF EQUITY ON FIRM VALUE WITH SIZE AS VARIABLE MODERATION (STUDY ON FOOD AND BEVERAGES COMPANIES 2017-2021) - Oktoriza, Linda Ayu; Puspitasari, Diana (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
This research aims to explain the effect of debt-to-asset ratio, stock price, and return of equity on firm value with size as variable moderation. The object study is a company food and beverages sector, that has been registered on the IDX for the 2017-2021 period.  This study wearing Multiple Regression Analysis and Moderated Regression Analysis using the SPSS program for processing the data. The results of the study prove that DER, Stock Price, ROE, and Size have an effect on Firm Value. Variables Stock price, ROE, and firm size have a positive effect on firm value. While DER has a negative influence on firm value. Firm size can moderate the DER relationship to Firm Value but cannot moderate the Share Price to Firm Value relationship.